Pengintegrasian semula dalam kalangan bekas banduan: satu tinjauan sorotan literatur - Nur Addila Ahmad,; N.K. Tharshini, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Inmates have been leaving correctional facilities and returning to their communities for as long as incarceration has existed. In general, reintegration is a difficult process for many former inmates since they face a variety of challenges simultaneously. Hence, this article is prepared to review the reintegration issue among former inmates. A literature review was conducted to obtain information on various reintegration issues from the Taylor and Francis, Sage, and Google Scholar databases. The result depicts that many former inmates have difficulties in finding employment because they tend to be uneducated and have low job skills. The findings also show that a large number of former inmates encounter difficulties in finding housing due to stigmatisation and a lack of family and community support. As an overall impact, the review is expected to have significant implications and provide a better understanding on the challenges related to reintegration process to the stakeholders hence they are able to design an impactful reintegration program to help former inmates adjust to life outside of prison and learn to desist from further criminal activities.